Morphology of long lasting mesoscale convective system under weak synoptic forcing over the Gangetic plain in May 2010 during the STORM-2010 campaign - GOYAL, SUMAN; SIKKA, DR; TYAGI, AJIT (MAUSAM, 2014)
A case study of long-lasting cloud cluster with embedded severe thunderstorms is conducted using the satellite data to demonstrate the efficacy of tracking such systems for help in nowcasting severe weather. The system had some unique features as it originated over Uttarakhand region (6 May 2010, 1300 UTC), travelled all across the Indo-Gangetic plains and reaching up-to Odisha/Bangladesh 24 to 36 hrs after its origin. The signature of the satellite information is analyzed in terms of cloud top temperature (CTT) from Kalpana-1 and associated rainfall from Tropical Rainfall Measuring Mission (TRMM) data. Intensity of the system is determined with the analysis of meteorological observations, automatic weather station (AWS), airport weather reports, autographic data and the meteorological tower data at Ranchi and Kharagpur. The use of satellite data provided one of the primary information for determining the intensity of the system and its areal dimensions. The paper discusses the evaluation of the convective system through its life history in some detail. In its long life, the convective system becomes intense in two phases. The first phase was over western Uttar Pradesh (UP) and the second phase was over Bihar, Jharkhand West Bengal belt. Radar information is used for the second phase of intensification as the system came under surveillance of Kolkata radar.